A PRAGMATIC STUDY OF FIGURATIVE LANGUAGE IN ANONYMOUS MOVIE SCRIPT - Ahmad Fauzi Jamaluddin; Maryadi Maryadi; Siti Zuhriah Ariatmi (Academy of Education Journal, 2017)
The research aims at describing the types of figurative language, implicature, and flouting maxim of Anonymous movie. The research employs the descriptive qualitative as the type of the research. The data source of this research is the script of Anonymous movie. Techniques of collecting data are watching the Anonymous movie, searching then downloading the Anonymous movie script, reading the Anonymous movie script, identifying the types of figurative languages in the movie script and underlying them, typing those figurative languages in paper, describing the types of figurative language by using Perrine theory and coding the data. The techniques of data analysis are describing the types of figurative language found in the Anonymous Movie Script, the writer uses Perrine theory (1977), describing the types the implicature, the writer refers to the theory of Grice (1989), and drawing discussion, describing the flouting maxim, the writer uses Cutting’s theory (2002). The data are shown with the italic, bold and underline words. One datum analysis presents figurative language, implicature and flouting maxim analysis. So, it doesn’t analyze separately. The result of the study shows that 1) the types of figurative language are: Metaphor (30.56%) which always uses an implicit comparison at the movie’s mind. The second position is Hyperbole (27.78%), and the third position is Simile (19.44%) and the fourth position is Personification (16.67%). Based on the frequency of occurrence, Irony (5.56%) is in the last position. 2) The all implicature of figurative languages cover conversational implicature (100%) and none of them are conventional implicature (0%). The conversational implicature divided into: particularized conversational implicature (94.44%) and generalized conversational implicature (5.56%) (3) The flouting maxim are used by the characters: flouting maxim of quality (86.11%), flouting maxim of relation (5.56%), flouting maxim of manner (5.56%), flouting maxim of quantity (2.78%).